REGULATION ANALYSIS ON OPERATIONAL LICENSES OF BECAK MOTOR IN TIDORE KEPULAUAN: PERSPECTIVE OF LAW NO. 12 YEAR 2011 - SEBAN, ULFA; ROSYIDI, IRHAM; RUMKEL, NAM (Awang Long Law Review, 2020)
The purpose of paper is to analyze the control costs for becak motor transportation operational permits in accordance with the authorities owned and the suitability of the contents of the Tidore Islands Mayor Regulation Number 3 Year 2016 concerning v Operational Permits with Types and Hierarchy in the Formation of Legislative Regulations. The type of research used is socio-juridical research, which is research that is focused on examining the application of the rules or norms in positive law. This research uses a statutory approach and a case approach. The data collected is then analyzed qualitatively, namely data obtained from both library research is grouped and selected then combined with the problems to be studied according to quality and truth so that they will answer the existing problems. The Regional Government of Tidore City does not have the authority to collect fees for controlling the operational license for becak motor vehicles because these charges are against the provisions of Article 2 paragraph (3) and Article 150 of Law Number 28 Year 2009 concerning Regional Taxes and Regional Levies and Article 286 paragraph 2) Law Number 23 Year 2014 concerning Regional Government, in which the authority to determine other types of levies other than those regulated in law is centralized through non-decentralized Government Regulations through regional legal products. So that the regional head regulation that regulates the collection of costs for controlling the operational license for becak motor does not have a legal standing. The type of becak motor vehicle is not classified into the type of vehicle that can function as public transportation as stipulated in Article 47 paragraph (3) of Law Number 22 Year 2009 concerning Traffic and Road Transportation so that the regulation of the becak motor Operational Permit contained in the Mayor of Tidore Islands Regulation Number 3 Year 2016 concerning the becak motor Operational Permit is disharmonious with the regulations in Law Number 22 Year 2009 Traffic and Road Transportation There is a discrepancy between the types and the content contained in the Mayor of Tidore Islands Regulation Number 3 Year 2016 concerning this becak motor Operational Permit where it is not there is an order from a higher level statutory law or regional law or not established based on authority. So that its existence should not be recognized as stipulated in Article 8 paragraph (2) of Law Number 12 Year 2011 concerning the Formation of Shrimp Legislation.